Restriction-modification systems in Mycoplasma spp - Brocchi,Marcelo (2007)
Restriction and Modification (R-M) systems are present in all Mycoplasma species sequenced so far. The presence of these genes poses barriers to gene transfer and could protect the cell against phage infections. The number and types of R-M genes between different Mycoplasma species are variable, which is characteristic of a polymorphism. The majority of the CDSs code for Type III R-M systems and particularly for methyltransferase enzymes, which suggests that functions other than the protection against the invasion of heterologous DNA may exist. A possible function of these enzymes could be the protection against the invasion of other but similar R-M systems. In Mycoplasma hyopneumoniae strain J, three of the putative methyltransferase genes were clustered in a region forming a genomic island. Many R-M CDSs were mapped in the vicinity of transposable elements suggesting an association between these genes and reinforcing the idea of R-M systems as mobile selfish DNA. Also, many R-M genes present repeats within their coding sequences, indicating that their expression is under the control of phase variation mechanisms. Altogether, these data suggest that R-M systems are a remarkable characteristic of Mycoplasma species and are probably involved in the adaptation of these bacteria to different environmental conditions.